2012
DOI: 10.3899/jrheum.120197
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantified Noncalcified Coronary Plaque in Systemic Lupus Erythematosus

Abstract: Objective A major cause of morbidity and mortality in systemic lupus erythematosus (SLE) is accelerated coronary atherosclerosis. New technology (computed tomographic angiography) can measure noncalcified coronary plaque (NCP), which is more prone to rupture. We report on a study of semiquantified NCP in SLE. Methods Patients with SLE (n = 147) with no history of cardiovascular disease underwent 64-slice coronary multidetector computed tomography (MDCT). The MDCT scans were evaluated quantitatively by a radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…119 The homocysteine levels did not differ compared with the patients who were not on methotrexate. This was a surprising finding due to the well-documented reduced risk of cardiovascular events in patients with rheumatoid arthritis who were treated with methotrexate.…”
Section: Prevention and Treatmentmentioning
confidence: 83%
“…119 The homocysteine levels did not differ compared with the patients who were not on methotrexate. This was a surprising finding due to the well-documented reduced risk of cardiovascular events in patients with rheumatoid arthritis who were treated with methotrexate.…”
Section: Prevention and Treatmentmentioning
confidence: 83%
“…CAC alone is not reflective of the absolute burden of atherosclerosis and studies from the general population suggest non-calcified coronary plaque (NCP) may be more important [35,36]. In SLE, multi-detector CT technology has shown that 53% (N=52/99) of patients without CAC have evidence of NCP, compared to 96% of patients with CAC [37]. Studies from the general population, however, suggest a much lower prevalence of NCP, where 6.5 to 16% have NCP in the absence of CAC [38,39], again demonstrating the greater burden of atherosclerosis in SLE.…”
Section: Coronary Artery Calcificationmentioning
confidence: 99%
“…In a cross-sectional study among patients in the Hopkins lupus cohort, one hundred and forty-seven patients underwent semiquantified assessment of noncalcified coronary plaque by 64-slice multi-detector computed tomography [24]. This included the baseline samples of the patients reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Patient age (P= 0.0001), current methotrexate use (P= 0.0005), history of anti-dsDNA positivity (P = 0.019) and obesity (assessed by body mass index, P= 0.058) were associated with the presence of noncalcified coronary plaque, in the multivariate model. Use of hydroxychloroquine and prednisone had no effect on the quantification of noncalcified coronary plaque [24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation